Low Complexity Adaptive Noise Canceller for Mobile Phones Based Remote Health Monitoring - Jafar Ramadhan Mohammed (Institute of Advanced Engineering and Science, 2014)
Mobile phones are gaining acceptance to become an effective tool for remote health monitoring. On one hand, during electrocardiographic (ECG) recording, the presence of various forms of noise is inevitable. On the other hand, algorithms for adaptive noise cancellation must be shared by limited computational power offered by the mobile phones. This paper describes a new adaptive noise canceller scheme, with low computational complexity, for simultaneous cancellation of various forms of noise in ECG signal. The proposed scheme is comprised of two stages. The first stage uses an adaptive notch filters, which are used to eliminate power-line interference from the primary and reference input signals, whereas the other noises are reduced using modified LMS algorithm in the second stage. Low power consumption and lower silicon area are key issues in mobile phones based adaptive noise cancellation. The reduction in complexity is obtained by using log-log LMS algorithm for updating adaptive filters in the proposed scheme. A comprehensive complexity and performance analysis between the proposed and traditional schemes are provided.DOI:http://dx.doi.org/10.11591/ijece.v4i3.5534